1993
DOI: 10.1016/s0006-3495(93)81329-8
|View full text |Cite
|
Sign up to set email alerts
|

Subfibrillar structure of type I collagen observed by atomic force microscopy

Abstract: We have imaged native rat tail and reconstituted bovine dermal type I collagen by atomic force microscopy, obtaining a level of detail comparable to that obtained on the same samples by transmission electron microscopy. The characteristic 60-70 nm D periodicity consists of ridges exhibiting high tip-sample adhesion alternating with 5-15-nm-deep grooves having low adhesion. We also observe an intraperiod or "minor" band consisting of 1-nm-deep grooves, and "microfibrils" arranged parallel to or inclined approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
85
0
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(97 citation statements)
references
References 18 publications
8
85
0
4
Order By: Relevance
“…Mature collagen fibrils are formed by the polymerization of collagen molecules staggered by D (about 67 nm, 1/4.4 of the molecular length) from each other, and hence showing D-periodicity. The D-periodic repetition of elevated and depressed surfaces along the collagen fibrils, corresponding to overlap (materially dense) and gap (materially sparse) regions, respectively, has been revealed by AFM (BASELT et al, 1993). In the present study, the probable interaction of type VI collagen with D-periodic collagen fibrils through PGs/GAGs was topologically shown by the increase in the depth of the groove after hyaluronidase digestion using AFM imaging.…”
supporting
confidence: 58%
“…Mature collagen fibrils are formed by the polymerization of collagen molecules staggered by D (about 67 nm, 1/4.4 of the molecular length) from each other, and hence showing D-periodicity. The D-periodic repetition of elevated and depressed surfaces along the collagen fibrils, corresponding to overlap (materially dense) and gap (materially sparse) regions, respectively, has been revealed by AFM (BASELT et al, 1993). In the present study, the probable interaction of type VI collagen with D-periodic collagen fibrils through PGs/GAGs was topologically shown by the increase in the depth of the groove after hyaluronidase digestion using AFM imaging.…”
supporting
confidence: 58%
“…Experimental work conducted by Orgel, Fratzl and others have proved that all collagen-based tissues are organized into hierarchical structures, where the lowest hierarchical level consists of triple helical collagen molecules (Fratzl, 2008;Orgel et al, 2006;Orgel et al, 2001) and the multiscale structure is defined as TC/fibrils/fibres. Also, other authors have observed a longitudinal microfibrillar structure with a width of 4 -8 nm (Habelitz et al, 2002;Baselt et al, 1993). Three-dimensional image reconstructions of 36 nm-diameter corneal collagen fibrils also showed a 4 nm repeat in a transverse section that was related to the microfibrillar structure (Holmes et al, 2001).…”
Section: Mineralized Collagen Microfibrilmentioning
confidence: 71%
“…The extracellular collagen molecule, procollagen, is made up of three left-handed helix polypeptides, the so-called α-chains, coiled-up in a right-handed helical structure, about 300 nm long and 1.5 nm in diameter (Bella et al, 1994;Orgel et al, 2001;Bhattacharjee & Bansal, 2005). Collagen molecules assemble along a given direction through covalent bonds to form collagen microfibrils, constituting the basic building block of collagen fibrils (Baselt et al, 1993;Hulmes et al, 1995;Orgel et al, 2006Orgel et al, , 2011. The collagen fibrils are gathered in the extracellular matrix to form bundles of collagen fibers.…”
Section: Motivationmentioning
confidence: 99%